Genotoxic evaluations in Wistar rats of the hallucinogenic plant extract ayahuasca - Aline Pic-Taylor; Willian Melo Junior; José Souza-Filho; Cesar Koppe Grisolia; Eloisa Dutra Caldas (International Journal of Phytomedicine, 2016)
Ayahuasca, a psychoactive infusion, is a sacrament used by indigenous and non-indigenous communities in Brazil and other countries. This beverage has vaunted healing properties; however, its use in a therapeutic context still lacks preclinical data to certify its safety and effectiveness. This study evaluated the genotoxic, mutagenic and cytotoxic potential of ayahuasca in Wistar rats after a single oral dose. Rats of both sexes were randomly distributed into five experimental groups (n=10): negative control that received filtered water, positive control that received doxorubicin and treated groups that received ayahuasca at 1, 5 and 15 times the usual dose taken in human religious rituals. The rats were euthanized 30 hours after dosage. Genotoxicity was evaluated by flow cytometry, comet assay and micronucleus test. Renal, hepatic and pancreatic functions were evaluated by serum analysis. Ayahuasca showed low genotoxicity, with an increased frequency of micronuclei only at the highest exposure level, and a non-observed-adverse-effect-level established at 5X the dose, or 1.5 mg/kg bw N,N-dimethyltryptamine a major component of the infusion. No cytotoxic effects were observed in the tested conditions. Furthermore, hepatic, renal and pancreatic functions remained without significant changes for all treated groups.